الامتيازات الاجنبية و المؤتمرات الدولية قبل فرض الحماية المزدوجة على المغرب الاقصى ( 1844م-1911م ) - شكم صفية; د/بن خليفة محمود (جامعة عمار ثليجي الاغواط, 2024)
Summary: The subject of our study revolved around foreign concessions and international conferences before the dual protection loan over Al-Aqsa Morocco 1844-1911, as Morocco witnessed in this period intense international tensions between European countries over influence and control over Al-Aqsa Morocco and focusing on the strategy followed by the imperialist countries in that period. It came at the beginning of its plans in the form of skirmishes and